Characterisation of an artesian groundwater system in the Valle de Iglesia in the Central Andes of Argentina - Hinzer, Ilka (2021)
Despite its location in the “Arid Diagonal” of South America, the Valle de Iglesia contains a number of artesian springs, the most important of which are the Baños Pismanta thermal springs, which release water at ~45 °C. Despite the scarcity of water resources in the Valle de Iglesia, there have been few attempts to study these springs in any detail. In this study,>50 springs are described, each characterised by small volcano-like mud structures up to 15 m tall. Hydrogeological and hydrochemical analyses of the groundwater system in the Valle de Iglesia were performed to improve our understanding of the subsurface water fow and of the connections between the subsurface water and the associated systems of faults and springs. Site measurements were made, and the concentrations of the main ions and trace elements were also determined by laboratory analysis of water samples. The samples obtained from the spring were rich in Na–HCO3–SO4 and Na–SO4–HCO3, but the surface water samples from the Agua Negra River were rich in Ca–SO4–HCO3. The temperature of the springs was in the range 20–45 °C. Both the temperatures and the ionic ratios are compatible with the presence of a deep hydraulic circulation system. The oxidation of sulphide minerals nearby the magmatic rocks and volcanic edifces causes the mobilisation of arsenic, which accumulates in the groundwater due to the low annual rainfall. The concentrations of arsenic in the spring water samples were therefore higher than the current limit set by the World Health Organisation, meaning that the water is not suitable for human consumption.